THE DECISION TO USE GO-PAY IS INFLUENCED BY PERCEPTIONS OF CONVENIENCE WITH INTEREST AS A MEDIATION VARIABLE - Zaenal Arief; Siti Nuryati (International Journal Multidisciplinary Science, 2023)
The purpose of this study is to examine how perceived convenience and interest as mediating variables affect consumers' decisions to use Go-Pay. Differential semantic association research is used in this type of research. In this study, primary data and secondary data are used. To collect 100 respondents as a research sample, a technique called purposive sampling was used in this study. The data analysis approach used in this study is the structural equation model (SEM) with SmartPLS 3.0 for Windows. The findings show that perceived convenience has a beneficial and significant impact on the decision to use go-pay, as well as a large and beneficial impact on interest, while interest does not have a significant impact on go-pay decision making.